2021
DOI: 10.3390/ijms22115454
|View full text |Cite
|
Sign up to set email alerts
|

Processed Animal Proteins from Insect and Poultry By-Products in a Fish Meal-Free Diet for Rainbow Trout: Impact on Intestinal Microbiota and Inflammatory Markers

Abstract: Sustainability of aquaculture is tied to the origin of feed ingredients. In search of sustainable fish meal-free formulations for rainbow trout, we evaluated the effect of Hermetia illucens meal (H) and poultry by-product meal (P), singly (10, 30, and 60% of either H or P) or in combination (10% H + 50% P, H10P50), as partial replacement of vegetable protein (VM) on gut microbiota (GM), inflammatory, and immune biomarkers. Fish fed the mixture H10P50 had the best growth performance. H, P, and especially the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 78 publications
(105 reference statements)
5
41
1
2
Order By: Relevance
“…Such taxa have also been identified in BSF whole larvae/prepupae or their gut [ 67 70 ]. The microbiota in all diets contained Photobacterium , but made up more than 50% of the microbiota in the control feed, similar to previous reports [ 60 ]. Photobacterium is widely distributed in marine environment and fish [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Such taxa have also been identified in BSF whole larvae/prepupae or their gut [ 67 70 ]. The microbiota in all diets contained Photobacterium , but made up more than 50% of the microbiota in the control feed, similar to previous reports [ 60 ]. Photobacterium is widely distributed in marine environment and fish [ 71 , 72 ].…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed that inclusion of meals and fractions of insects in the diet can modify the gut microbiota of Atlantic salmon pre-smolts. Previous findings also showed that feeding BSF modulated gut microbiota in rainbow trout [ 27 29 , 41 , 60 ] and salmon post-smolts [ 26 ]. The phyla Firmicutes , Proteobacteria , Actinobacteriota , and Bacteroidota represented more than 94% of the gut microbiota in fish, regardless of the diet, which belong to the core gut microbiota in different fish species [ 22 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The soybean protein content in soybean meal is between 43.0% and 55.0%, and most of them are water-soluble proteins. Besides protein, they also contain other rich nutrients, which is a good dietary protein source for fish and monogastric animals [ 25 , 26 ]. Therefore, it is of crucially practical significance to explore the effects of soybean meal instead of fish meal on the intestinal microbial diversity of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the feed products on the market today do not contain processed animal proteins (PAPs), which are approved to be used in fish feed. Insect protein has similar properties to PAPs and is a good, sustainable substitute [ 26 , 27 ] and an excellent source of energy and digestible amino acids for livestock. Since insect proteins were approved for use in aqua feed, European insect farmers have commercialized about 1000 tonnes of insect protein.…”
Section: Project Contribution Beyond the State-of-the-artmentioning
confidence: 99%